Social Class in Organizations: Entrance, Promotion, and Organizational and Societal Consequences of the Corporate Elite. (October 2021) - Lee, Michelle K.; Kish-Gephart, Jennifer J.; Mizruchi, Mark S.; Palmer, Donald A.; Useem, Michael
Organizational theorists studying executives of large corporations have long theorized that top management is dominated by elites of upper social class background. Organizations reflect the class system in the societies they are situated in by advantaging those of higher social class background. If organizations are perpetuating societal inequality by favoring those from higher social class and positioning them to dictate organizational outcomes, it is important to understand ways to reduce inequality by increasing social class diversity, and theorize on the implications of this diversity for business and society. This article brings together scholars on the forefront of social class research to understand the influence of social class on the corporate elite. The scholars explore the effect of social class in attaining access to the most influential managerial positions, conditions that enable greater diversity, and how the corporate elite can affect firm strategic actions and key societal outcomes.